Low Resistance to First and Second Line Anti- Tuberculosis Drugs among Treatment Naive Pulmonary Tuberculosis Patients in Southwestern Uganda - Orikiriza, Patrick; Tibenderana, Becky; Siedner, Mark J.; Mueller, Yolanda; Byarugaba, Frederick; Moore, Christopher C.; Evans, Emily E.; Bonnet, Maryline; Page, Anne-Laure; Bazira, Joel; II, Yap Boum (PLoS ONE, 2015)
Background: There are limited data on region-specific drug susceptibility of tuberculosis (TB) in Uganda. We performed resistance testing on specimens collected from treatment-naive patients with to provide data to guide regional recommendations for empiric TB therapy. Methods: Archived isolates, obtained from patients at Mbarara Regional Referral Hospital from February 2009 to February 2013, were tested for resistance to isoniazid and rifampicin using the MTBDRplus and Xpert MTB/RIF assays. A subset of randomly selected isolates was tested for second line agents, including fluoroquinolones (FQs), aminoglycosides, cyclic peptides, and ethambutol using the MTBDRsl assay. We performed confirmatory testing for FQ resistance using repeated MTBDRsl, the Mycobacteria growth indicator tube (MGIT) assay, and sequencing of the gyrA and gyrB genes. Results: We tested isolates from 190 patients. The cohort had a median age of 33 years (IQR 26- 43), 69% (131/190) were male, and the HIV prevalence was 42% (80/190). No isolates (0/190) were rifampicin-resistant and only 1/190 (0.5%) was isoniazid-resistant. Among 92 isolates tested for second-line drug resistance, 71 (77%) had interpretable results, of which none were resistant to aminoglycosides, cyclic peptides or ethambutol. Although 7 (10%) initially tested as resistant to FQs by the MTBDRsl assay, they were confirmed as susceptible by repeat MTBDRsl testing as well as by MGIT and gyrase gene sequencing Conclusion: We found no MDR-TB and no resistance to ethambutol, FQs, or injectable anti-TB drugs in treatment naïve patients with pulmonary TB in Southwestern Uganda. Standard treatment guidelines for susceptible TB should be adequate for most patients with TB in this population. Where possible, molecular susceptibility testing methods should be routinely validated by culture methods
Keywords: First and Second Line Anti- Tuberculosis Drugs; Pulmonary Tuberculosis Patients; Xpert MTB/RIF assays; MTBDRplus; Uganda